STUDYING THE TRANSFORMATION OF THE SOIL COVER IN GRAIN-FALLOW CROP ROTATION - Nazarova, A. N. (Science and education., 2019)
The state of the soil cover and the level of soil fertility largely determine the productivity of cultivated crops and the level of development of the agro-industrial complex. Modern soils undergo significant changes in the process of development and usage in agricultural production. Food security of the Republic of Kazakhstan is largely determined by the quality of agricultural lands, which, in turn, depends on the anthropogenic load. Both excessive and insufficient investment of energy subsidies in the agro-ecosystem can lead to negative consequences of the agronomic and environmental plan. In the last decade, significant damage to the soil cover is caused by irrational farming, violations of agricultural technologies associated with the changed economic situation in the country and the deterioration of environmental conditions. This leads to changes in many physical and chemical properties of dark chestnut soils. There is a decrease in the humus content, saturation of the soil absorbing complex with exchange bases, indicators of effective soil fertility. The water balance is disturbed due to the transformation of the physical properties of dark chestnut soils for the worse. Therefore, it is necessary to contribute to the preservation of soil fertility as efficiently as possible. In this regard, the role of monitoring studies that allow timely detection of changes in the level of fertility, if necessary, to develop appropriate corrective measures, as well as to predict the state of the system in the future. Studies have established the transformation of agrochemical and agrophysical indicators of soil cover during long - term use in grain-steam crop rotation.Состояние почвенного покрова, уровень плодородия почв во многом определяют продуктивность возделываемых сельскохозяйственных культур, уровень развития агропромышленного комплекса. Современные почвы претерпевают значительные изменения в процессе освоения и использования в сельскохозяйственном производстве. Продовольственная безопасность Республики Казахстан в значительной степени определяется качественным состоянием сельскохозяйственных угодий, которое, в свою очередь, зависит от антропогенной нагрузки. Как избыточное, так и недостаточное вложение энергетических субсидий в агроэкосистему может привести к возникновению негативных последствий агрономического и экологического плана. В последние десятилетие значительный ущерб почвенному покрову наносится следствие нерационального ведения хозяйства, нарушения земледельческих технологий, связанных с изменившейся экономической ситуацией в стране и ухудшением экологических условий. Это приводит к изменению многих физико-химических свойств темно-каштановых почв. Отмечается снижение содержания гумуса, насыщенности почвенного поглощающего комплекса обменными основаниями, показателей эффективного плодородия почв. Нарушается водный баланс, в связи с трансформацией физических свойств темно-каштановых почв в худшую сторону. Поэтому необходимо как можно более эффективно по способствовать сохранению почвенного плодородия. В связи с этим повышается роль мониторинговых исследований, которые позволяют своевременно выявить изменения уровня плодородия, при необходимости разработать соответствующие корректирующие мероприятия, а также спрогнозировать состояние системы в перспективе. Исследованиями установлено трансформация агрохимических и агрофизических показателей почвенного покрова при длительных использованиях в зерно-паровом севообороте.
Keywords: научный журнал; почвоведение; отечественное издание; плодородие почв; периодическое издание; продуктивность сельскохозяйственных культур; журнал кксон; гумус почв; transformation; agrochemical indicators; dark chestnut soils; humus